Establishment of a cell line with high transfection efficiency from zebrafish Danio rerio embryos and its susceptibility to fish viruses. Issue 4 (17th August 2017) - Jin, Y. L.; Chen, L. M.; Le, Y.; Li, Y. L.; Hong, Y. H.; Jia, K. T.; Yi, M. S.
Abstract : A cell line ZBE3 isolated from a continuous cell culture derived from zebrafish Danio rerio blastomeres by clonal growth was characterized. ZBE3 cells had been subcultured for >120 passages since the initial primary culture of the blastomeres. The ZBE3 cells grow stably at temperature from 20 to 32° C with an optimum temperature of 28° C in ESM2 or ESM4 medium with 15% foetal bovine serum (FBS). The optimum FBS concentration for ZBE3 cell growth ranged from 15 to 20%. Cytogenetical analysis indicated that the modal chromosome number of ZBE3 cells was 50, the same as the diploid chromosome number of D. rerio . Significant cytopathic effect was observed in ZBE3 cells after infection with redspotted grouper nervous necrosis virus, Singapore grouper iridovirus and grass carp reovirus, and the viral replication in the cells was confirmed by real‐time quantitative PCR and transmission electron microscopy, indicating the susceptibility of ZBE3 cells to the three fish viruses. After transfected with pEGFP‐N3 plasmid, ZBE3 cells showed a transfection efficiency of about 40% which was indicated by the percentage of cells expressing green fluorescence protein. The stable growth, susceptibility to fish viruses as well as high transfection efficiency make ZBE3 cells be a useful tool in transgenic manipulation, fish virus‐host cell interaction and immune response in fish.